The results of using self-stigma reduction programs of HIV infected people in Akat Amnauy Hospital, Sakon Nakhon Province - Suttawanit, Jirattikal; Phanawong, Nava (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Thailand has been fighting AIDS for more than 30 years, with some success in lowering the number of new HIV cases and deaths, but the country still has a high HIV infection rate and struggles with unfair discrimination linked to both HIV and gender. Methods: This action research was undertaken to reduce self-stigmatization of HIV-infected people in Akat Amnuay Hospital. The participants included 67 infected HIV cases at Antiretroviral clinic. Data collection was conducted from June 2022 to December 2022. Data collection from group activity, and individual follow-up. Qualitative data were analyzed by classification, inferential analyzing, interpret meaning, conclusions and explain explorer. Descriptive statistics and paired t-tests were analysis. Results: The study found that Self stigma reduction programs of HIV infected people gained an understanding of the stages of self-management, enabling them to resolve issues correctly and have a positive impact on their own health. It also found that participants’ self-stigma scores before and after the intervention differed significantly, and that self-stigmatism decreased significantly at.000. Conclusions: The development of one’s own power is one of the results of a program to reduce self-stigma. by spending more time dealing with unfavorable attitudes. Recognize your own worth and adopt a positive outlook. It is advantageous for hospital staff who oversee the HIV clinic to put in place a procedure for lowering self-stigma in new patients, patients who have missed appointments, and patients who take the medication erratically and experience complications.